PENDIDIKAN NILAI SOSIAL BUDAYA DALAM KELUARGA DAN LINGKUNGAN MASYARAKAT SUKU NUAULU DI PULAU SERAM - Jenny Koce Matitaputty (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2016)
This study aimed to revea l the information about educational of Nuaulu clan communities in Ceram Island, Central Maluku regency which still hold their high socio-cultural value. How do they pass, teach and construct all socio-cultural value to their next generation in order they can still maintain what they have so it can grew together one another in peace and harmony? To answer these questions, the researcher needed to explore more detail in understanding about Nuaulu clan in socio-cultural educational in their family and environment around them. Research metodologi used in this research was qualitative research by using study cases appropriate. Based on the analysis of issue, the researcher stateted the key informants were selected by purposive with snowball sampling based on the consideration of the fasibility and research purposes, namely the case of the five family of Nuaulu clan which have a central role in the lives of community of Nuaulu clan. While the supporting informants were those who consider worthy of giving information related to the research objectives. Based on the result of the data, Education and Socio-cultural Value (ESDV) with in the families and the rest of Nuaulu society had been done through ritual of traditional ceremony as signed to meet and individual growth in their live especially since pregnancy (9 months), birth, adult (women and men) and marriage as well as their characteristic of the seven elements of culture. The result of this research shown that there were several meaningful traditional ceremonies and characteristics Nuaulu clan. The great value was relefan, integrative and contributive to the socio-cultural value of education, so it needs to be developed.